2014
DOI: 10.15580/gjer.2014.2.021914117
|View full text |Cite
|
Sign up to set email alerts
|

Developing Module of Practical Chemistry Physics SETS Vision Activity to Increase Science Process Skills of Student Teacher

Abstract: Competencies required for prospective chemistry teachers include enhancer chemistry learning in the laboratory and field, designing experiment for learning or research, and carrying out experiments in the right method. For the time being, the implementation of Physical Chemistry lab work in Chemical Education Departmen of IAIN Walisongo was conducted through recipes models. Practical guidance and instrument have been provided by laboratory. The model therefore fosters less spirit in searching knowledge. To ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Learning with PBL using SETS-based modules makes it easier for students to understand the material being taught, improves students 'thinking skills about aspects of science, and increases students' activeness in the learning process (Abualrob & Shah, 2012;Pedretti & Bellomo, 2013;Widiyanti et al, 2015). Several previous studies (Amrullah et al, 2017;Sari et al, 2016;Susilogati et al, 2014;Sutikno & Setyasto, 2019) also revealed that learning with modules will help students learn actively, independently, giving students opportunities to conduct experiments, discussions, and deepen understanding of concepts that can improve student achievement and critical thinking skills.…”
Section: Figure-2 the Mean Of Pretest Post-test And N-gain Scoresmentioning
confidence: 94%
“…Learning with PBL using SETS-based modules makes it easier for students to understand the material being taught, improves students 'thinking skills about aspects of science, and increases students' activeness in the learning process (Abualrob & Shah, 2012;Pedretti & Bellomo, 2013;Widiyanti et al, 2015). Several previous studies (Amrullah et al, 2017;Sari et al, 2016;Susilogati et al, 2014;Sutikno & Setyasto, 2019) also revealed that learning with modules will help students learn actively, independently, giving students opportunities to conduct experiments, discussions, and deepen understanding of concepts that can improve student achievement and critical thinking skills.…”
Section: Figure-2 the Mean Of Pretest Post-test And N-gain Scoresmentioning
confidence: 94%
“…Learning with PBL using SETS-based modules makes it easier for students to understand the material being taught, improves students 'thinking skills about aspects of science, and increases students' activeness in the learning process (Abualrob & Shah, 2012;Pedretti & Bellomo, 2013;Widiyanti et al, 2015). Several previous studies (Amrullah et al, 2017;Sari et al, 2016;Susilogati et al, 2014;Sutikno & Setyasto, 2019) also revealed that learning with modules will help students learn actively, independently, giving students opportunities to conduct experiments, discussions, and deepen understanding of concepts that can improve student achievement and critical thinking skills. The research data shows that the implementation of the SETS-based module with the PBL model is able to develop students' critical thinking skills.…”
Section: Analysis Of Critical Thinking Skillsmentioning
confidence: 94%
“…Those results showed that the learning was effective. Susilogati, et al (2014) stated that teaching SETS (Science, Environment, Technology, and Society) course could encourage students to do investigations to gain knowledge. The average scores for the six sta- Table 6.…”
Section: The Effectiveness Of the Learning Devicesmentioning
confidence: 99%